1993
DOI: 10.1002/jmri.1880030213
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of phase‐contrast flow measurements in the presence of partial‐volume effects

Abstract: The accuracy of volume flow rate measurements obtained with phase-contrast methods was assessed by means of computer simulation and in vitro experiments. Factors studied include (a) the partial-volume effect due to voxel dimensions relative to vessel dimensions and orientation and (b) intravoxel phase dispersion. It is shown that limited resolution (partial-volume effect) is the major obstacle to accurate flow measurement for both laminar and plug flow. The results show that at least 16 voxels must cover the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
242
1
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(256 citation statements)
references
References 13 publications
7
242
1
5
Order By: Relevance
“…To obtain accurate results, Tang et al (31) recommend ensuring that the flow region is covered by at least 16 isotropic voxels to minimize partial volume effects within the flow region. This recommendation was fulfilled for the PC-MRA measurements at the inlet, outlet 3, and the aneurysm, though not for outlet 1 (nine voxels) and outlet 2 (12 voxels).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain accurate results, Tang et al (31) recommend ensuring that the flow region is covered by at least 16 isotropic voxels to minimize partial volume effects within the flow region. This recommendation was fulfilled for the PC-MRA measurements at the inlet, outlet 3, and the aneurysm, though not for outlet 1 (nine voxels) and outlet 2 (12 voxels).…”
Section: Discussionmentioning
confidence: 99%
“…Vessel-slice obliquity is a recognized source of partial volume effects as described (31), with the severity dependent on vessel size and the voxel dimensions of the image. This is a probable explanation for the poor performance in outlet 1, which was measured with a significant angle between the imaging plane and the artery's main flow direction.…”
Section: Discussionmentioning
confidence: 99%
“…Low spatial resolution may account for the inaccurate flow measurements obtained using the spinwarp acquisition. It has been demonstrated that flow measurements will be inaccurate if an insufficient number of pixels spans the vessel of interest (11).…”
Section: Discussionmentioning
confidence: 99%
“…The accurate measurement of flow requires high spatial resolution for a true depiction of the cross-sectional area of the vessel of interest (11). In addition, a high temporal resolution is required for an accurate representation of the varying shape of a flow waveform throughout the cardiac cycle.…”
mentioning
confidence: 99%
“…The accuracy of such methods is limited by data quality and the spatial resolution of the velocity estimates. Particularly, phase contrast (PC) MRI suffers from partial-volume effects (17) and inadequate signal-to-noise ratio (SNR) at high spatial resolutions (Fig. 1).…”
mentioning
confidence: 99%